The histological changes in the kidney and liver of Quail induced by Malathion (NTU Journal of Agriculture and Veterinary Science, 2023)
This study was conducted to evaluat the toxic influenceof the applied malathion in the liver and kidney tissues in Quail. 18 Quails were distributed in 3 groups. 1 as a control group. Group 2 treated one day every week for 28 days. Group 3 treated one day every two week for 56 days. The result showed in G2 decreases in BW, G3 noticed increased in BW. G2 the hepatocytes plates architectures are disrupted appearances, congestion in sinusoid and in hepatic central vein. Enlargement of portal vein.in G3 showed moderate spread damage of hepatocytesand proliferation of bile duct. congestion in the portal vein & artery. The sinusoid & central vein was expanded & congested. degeneration in the endothelium of central vein. the histopathological changes in the kidney in G2 showing atrophied of the glomeruli ,congestion & infiltration ofl lymphocytes of some glomeruli, in G3 showing congestion , distraction & shrinkage of glomeruli. .In conclusion ;exposure of Quails to local malathion result in marked histopathological changes in G2 more than G3 in liver &kidney tissues and a significant injury in kidney tissues more than liver tissues .